(untitled) - Food and Agriculture Organization of the United Nations (Rome, Italy, 2008)
This report identifies the many positive and negative impacts of aquaculture with their far-reaching socio-economic implications. While they agreed that multi-criteria decision-making framework using analytical hierarchy process as a measurement technique is a suitable method for assessing socio-economic impacts of aquaculture, experts recognized that other methods such as the costs benefits analysis could also be used depending on circumstances.
Keywords: Aquaculture,Socio-economic impacts,Nuôi trồng thủy sản,Tác động kinh tế-xã hội